Penerapan Asas Praduga Tidak Bersalah (Presumption of Innocent) Pelaku Tindak Pidana Pencurian di Tingkat Penyidikan: Studi di Kepolisian Resort Pamekasan - Ahmad Faiz Alamsyah; Sidik Sunaryo; Yaris Adhial Fajrin (Indonesia Law Reform Journal, 2022)
The principle of the presumption of innocence is one of the principles regulated in the Criminal Procedure Code (KUHAP). The application of the principle of the presumption of innocence is closely related to the application of rights to individuals, for example to suspects in the crime of theft who are in the process of being investigated. The regulation of these rights is regulated concretely in the Criminal Procedure Code. However, despite this, the application of the principle of the presumption of innocence in this case the application of the rights of the suspect during the arrest and detention process is still not given much attention by police investigators. Therefore, the researcher raised two problem formulations. First, how is the application of every person arrested for committing the crime of theft to be considered innocent until there is an Inkracht Decision at the Pamekasan Police Resort. Second, how is the application of every person who is detained for the crime of theft must be considered innocent until the Inckracht Decision is made by the Pamekasan Resort Police. The research method used is a sociological juridical approach. It can be concluded that in the application of rights in the arrest process, two rights have not been implemented by the Pamekasan Police investigators, namely the suspect's right to ask the investigator to show an arrest warrant (Article 18 paragraph (1) KUHAP) and regarding the right for the family of the arrested suspect to receive a copy of the letter. an immediate arrest order (article 18 paragraph (3) KUHAP). While in the detention process, two rights have not been implemented, namely those related to the suspect's right to give information freely (article 52 KUHAP) and the suspect's right to obtain legal assistance and law enforcers are required to appoint legal counsel (article 54 KUHAP)